Tenofovir rescue therapy for chronic hepatitis B patients after multiple treatment failures - Kim, Yu Jin (World journal of gastroenterology : WJG, 2012)
AIM：To evaluate the efficacy and safety of tenofovir disoproxil fumarate（TDF） for chronic hepatitis B（CHB） patients after multiple failures.METHODS：A total of 29 CHB patients who had a suboptimal response or developed resistance to two or more previous nucleoside/nucleotide analogue（NA） treatments were included.Study subjects were treated with TDF alone（n = 13） or in combination with lamivudine（LAM,n = 12） or entecavir（ETV,n = 4） for ≥ 6 mo.Complete virologic response（CVR） was defined as an achievement of serum hepatitis B virus（HBV） DNA level ≤ 60 IU/mL by real-time polymerase chain reaction method during treatment.Safety assessment was based on serum creatinine and phosphorus level.Eleven patients had histories of LAM and adefovir dipivoxil（ADV） treatment and 18 patients were exposed to LAM,ADV,and ETV.Twenty-seven patients（93.1%） were hepatitis B e antigen（HBeAg） positive and the mean value of the baseline serum HBV DNA level was 5.5 log IU/mL ± 1.7 log IU/mL.The median treatment duration was 16 mo（range 7 to 29 mo）.RESULTS：All the patients had been treated with LAM and developed genotypic and phenotypic resistance to it.Resistance to ADV was present in 7 patients and 10 subjects had a resistance to ETV.One patient had a resistance to both ADV and ETV.The cumulative probabilities of CVR at 12 and 24 mo of TDF containing treatment regimen calculated by the Kaplan Meier method were 86.2% and 96.6%,respectively.Although one patient failed to achieve CVR,serum HBV DNA level decreased by 3.9 log IU/mL from the baseline and the last serum HBV DNA level during treatment was 85 IU/mL,achieving near CVR.No patients in this study showed viral breakthrough or primary non-response during the follow-up period.The cumulative probability of HBeAg clearance in the 27 HBeAg positive patients was 7.4%,12%,and 27% at 6,12,and 18 mo of treatment,respectively.Treatment efficacy of TDF containing regimen was not statistically different according to the presence of specific HBV mutations.History of prior exposure to specific antiviral agents did not make a difference to treatment outcome.Treatment efficacy of TDF was not affected by combination therapy with LAM or ETV.No patient developed renal toxicity and no cases of hypophosphatemia associated with TDF therapy were observed.There were no other adverse events related to TDF therapy observed in the study subjects.CONCLUSION：TDF can be an effective and safe rescue therapy in CHB patients after multiple NA therapy failures.